A formação contínua de professores na Amazônia Amapaense: uma proposta para a realidade Ribeirinha do Anauerapucu - Valente, Tatiane Nunes (2017)
The objective of this research is to elaborate and analyze a proposal for continuous education of teachers, considering the socio-educational context of the Foz do Rio Vila Nova riverside school, and to investigate in which ways the activities proposed in this study provided space for the transformation of the teaching practice of the participants during the educationalperiod. Thus, the research question is: from a proposal of continuous formation, how to collaborate for the practice of the teacher, considering the context of a riverside school?The school is located by the Vila Nova River, in the community of Anauerapucu, an hour from the Municipality of Santana by boat, in the State of Amapá, and offers Kindergarten and the first years of Elementary School.The research developed was based on the critical-collaborative approach (MAGALHÃES, 2006, 2011) and on the concept of Creative Chain (LIBERALI, 2012). The data collected were analyzed based on the critical reflection actions: Describe, Inform, Confront and Rebuild.The meetings were held through discussions of the pedagogical doing, in a critical-collaborative way, oriented to a reflection on the acting and the thinking of the teacher, searching for transformations that would help in the challenge of educating in the Amapaense Amazon.The results show that the educationalactivities allowed space for the study of theoretical conceptions, dialogue, exchange of knowledge and experiences, contributing forthe teachers to understand and discuss the reality of their classrooms.In addition, they have created a basis for teacher reflection about the educational difficulties.However, for the effective transformation of the teaching practice, a more in-depth formation is necessary from real problems of the daily school life, aspect not realized in the seven formative meetings, since it was not possible to approach practical questions of the classroom